Engineering three-dimensional bone macro-tissues by guided fusion of cell spheroids - Prabhakaran, Vinothini; Melchels, Ferry P.W.; Murray, Lyndsay M.; Paxton, Jennifer Z. (Frontiers in Endocrinology, 2023)
Introduction Bioassembly techniques for the application of scaffold-free tissue engineering approaches have evolved in recent years toward producing larger tissue equivalents that structurally and functionally mimic native tissues. This study aims to upscale a 3-dimensional bone in-vitro model through bioassembly of differentiated rat osteoblast (dROb) spheroids with the potential to develop and mature into a bone macrotissue. Methods dROb spheroids in control and mineralization media at different seeding densities (1 × 104, 5 × 104, and 1 × 105 cells) were assessed for cell proliferation and viability by trypan blue staining, for necrotic core by hematoxylin and eosin staining, and for extracellular calcium by Alizarin red and Von Kossa staining. Then, a novel approach was developed to bioassemble dROb spheroids in pillar array supports using a customized bioassembly system. Pillar array supports were custom-designed and printed using Formlabs Clear Resin® by Formlabs Form2 printer. These supports were used as temporary frameworks for spheroid bioassembly until fusion occurred. Supports were then removed to allow scaffold-free growth and maturation of fused spheroids. Morphological and molecular analyses were performed to understand their structural and functional aspects. Results Spheroids of all seeding densities proliferated till day 14, and mineralization began with the cessation of proliferation. Necrotic core size increased over time with increased spheroid size. After the bioassembly of spheroids, the morphological assessment revealed the fusion of spheroids over time into a single macrotissue of more than 2.5 mm in size with mineral formation. Molecular assessment at different time points revealed osteogenic maturation based on the presence of osteocalcin, downregulation of Runx2 (p < 0.001), and upregulated alkaline phosphatase (p < 0.01). Discussion With the novel bioassembly approach used here, 3D bone macrotissues were successfully fabricated which mimicked physiological osteogenesis both morphologically and molecularly. This biofabrication approach has potential applications in bone tissue engineering, contributing to research related to osteoporosis and other recurrent bone ailments.